Ecology and management of giant hogweed (Heracleum mantegazziannum) - Pyšek, Petr (CABI Pub., 2007)
This book is a compendium of the current knowledge on the invasive plant, giant hogweed (Heracleum mantegazzianum) that spread from Caucasus across Europe, creating serious problems displacing and overtaking native plants. Topics covered include: taxonomy, genetics, reproductive ecology, and invasion dynamics at regional and local scales. Intended for students, researchers and practitioners in agriculture, conservation, weed science and plant ecology, this book also reviews the possibilities of mechanical, chemical and biological control, and control by grazing.